The Influence of Physical Activity and Epigenomics On Cognitive Function and Brain Health in Breast Cancer - Wagner, Monica A.; Erickson, Kirk I.; Bender, Catherine M.; Conley, Yvette P. (Frontiers in Aging Neuroscience, 2020)
Risk of breast cancer increases with age, with the majority of women diagnosed with breast cancer being postmenopausal. It has been estimated that 25 to 75% of women with breast cancer experience changes in cognitive function (CF) related to disease and treatment, which compromises psychological well-being, decision making, ability to perform daily activities, and adherence to cancer therapy. Unfortunately, the mechanisms that underlie neurocognitive changes in women with breast cancer remain poorly understood, which in turn limits the development of effective treatments and prevention strategies. Exercise has great potential as a non-pharmaceutical intervention to mitigate the decline in CF in women with breast cancer. Evidence suggests that DNA methylation, an epigenetic mechanism for gene regulation, impacts CF and brain health (BH), that exercise influences DNA methylation, and that exercise impacts CF and BH. Although investigating DNA methylation has the potential to uncover the biologic foundations for understanding neurocognitive changes within the context of breast cancer and its treatment as well as the ability to understand how exercise mitigates these changes, there is a dearth of research on this topic. The purpose of this review is to compile the research in these areas and to recommend potential areas of opportunity for investigation.